TRAJECTORIES OF FUNCTIONAL IMPAIRMENT AND DEPRESSIVE SYMPTOMS IN RELATION TO SUBSEQUENT DEMENTIA RISK. (11th November 2018) - Cadar, D; Davies, H; Llewellyn, D; Batty, G; Steptoe, A
Abstract: The relationship between trajectories of functional impairments or depressive symptoms and future dementia is poorly understood. We employed Growth Mixture Modelling with a categorical distal outcome to identify independent group-based trajectories of activities of daily living (ADL); instrumental activities of daily living (IADL) or depressive symptoms over an 8-year period, in association with subsequent dementia up to four years later, using data from the English Longitudinal Study of Ageing. Participants (65+ years) with increasing IADL impairments or depressive symptoms (Class III), were more likely to be classified with subsequent dementia (Odds Ratios (OR); 95% confidence interval: 14.59; 8.21–20.97 and OR=3.94, 2.38–5.30) compared with those who maintained low levels of impairments or depressive symptoms (Class I). A higher risk was also observed for those who started with and maintained raised levels of functional impairment, or depressive symptoms (Class II). Increasing trajectories of functional impairments or depressive symptoms were associated with a higher subsequent risk of dementia, indicating a preclinical manifestation. Our results highlight the importance of monitoring both types of physical limitations (ADL and IADL) as well as emotional states and increase the awareness of the importance of upwards trajectories of functional impairments and depressive symptoms as possible markers for dementia onset.